Development of bank client service models in Ukraine: the comparison of Private Banking and VIP Banking - Меркулов, Данил Александрович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The comparative analysis of bank client service models in Ukraine is presented in the article. The basic elements of Private Banking иVIP Banking are considered; their main features are marked, advantages and shortcomings are discussed; conclusion about improvement of this models and their implementation in Ukraine are presented.